Using Video as Media of Teaching in English Language Classroom: Expressing Congratulation and Hopes - Kamelia Kamelia (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2019)
This research was design in descriptive qualitative research. The data was collected and analyzed from several related of literature on the application of videos in English classroom around the globe. This study stands its objectives and sees video as one of the effective media that can make students more enjoyed process teaching and learning. This study recorded that many research has proved on the effectiveness of using video as media for students, especially the EFL classroom. It seems using videos can give a relaxing situation for students in learning English. It also can make students more active and easy to understand the material since the video contains pictures and audio that causes students to see the material directly. These recent studies also share the teaching procedure used by the researcher/teacher when conducting teaching and learning activities in the class which are seems divided into three steps, e.g., Pre-activity, main activity, and activity of the last post. The analysis recommends the teacher, as a model should have planning systematically what teacher should do during teaching and learning process to deliver good material.